Hyper bio assembler for 3D cellular systems - Arai, Tatsuo; Arai, Fumihito; Yamato, Masayuki (Springer Japan, 2015)
Hyper Bio Assembler for Cellular Systems is the first book to present a new methodology for measuring and separating target cells at high speed and constructing 3D cellular systems in vitro. This book represents a valuable resource for biologists, biophysicists and robotic engineers, as well as researchers interested in this new frontier area, offering a better understanding of the measurement, separation, assembly, analysis and synthesis of complex biological tissue, and of the medical applications of these technologies. This book is the outcome of the new academic fields of the Ministry of Education, Culture, Sports, Science and Technology?s Grant-in-Aid for Scientific Research in Japan.